Pengaruh Arah Aliran dari 0 - 45 pada koefisien perpindahan kalor Konveksi di Permukaan Silinder - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
The effects of flow directions on the heat transfer coefficient on cylinder surface have been investigated. The heat transfer coefficient was evaluated with heat-mass transfer analogy. The cylinder was made of naphtalene. The direction of the flow was defined as the angle between the flow direction and a line perpendicular to the cylinder axis. Due to the influence of the cylinder holder on the flow pattern, the angle was limited from 00 to 45". The results show that the effects of the flow direction on the heat transfer coefficient was negligible.